IMPLEMENTASI STRATEGI EVERYONE IS A TEACHER HERE DALAM MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI SEKOLAH MENENGAH ATAS NEGERI 1 CIKARANG BARAT - Ahmad Hafizh; Iwan Hermawan; Kasja Eki Waluyo (Jurnal Al-Ulum : Jurnal Pemikiran dan Penelitian Ke-Islaman, 2023)
Islamic religious education in schools still encounters many problems in its implementation, as is the case in the learning process at schools which is currently still limited and monotonous which causes a lack of student participation in class. Therefore, PAI teachers at SMA Negeri 1 Cikarang Barat apply the everyone is a teacher here learning strategy, which is expected to stimulate students to play an active role in learning. The research method used in this research is qualitative with data collection methods: interviews, field observations and documentation analysis. While the informants from this research activity were PAI teachers as primary subjects and some students and principals of SMAN 1 Cikarang as secondary subjects. The results found in this study were that the implementation of the everyone is a teacher here strategy in PAI subjects at SMA Negeri 1 Cikarang Barat went well. In addition, there are several influencing factors, namely supporting factors and inhibiting factors. Supporting factors are complete infrastructure and professional attitude and teacher enthusiasm in educating. While the inhibiting factor is that some students are still reluctant to express their opinions. The implication of this researcher is that Islamic religious education is still loved by students so that it is no longer a makeshift subject.